УМУМИЙ ЎРТА ТАЪЛИМ МАКТАБЛАРИДА ФИЗИКАДАН ЛАБОРАТОРИЯ ДАРСЛАРИНИ САМАРАДОРЛИГИНИ ОШИРИШДА АЙРИМ МАТЕМАТИК ТУШУНЧАЛАРДАН ФОЙДАЛАНИШ МЕТОДИКАСИ - Деҳқонова, О. (SCIENCE and SOCIETY, 2022)
The article deals with the concepts of mathematics in conducting and analyzing physics classes in secondary schools. In order to ensure the continuity of physics and mathematics, we must pay attention to the sequence of topics in these textbooks. The following analyzes the relevance of topics in physics and mathematics in secondary schools.
Keywords: interconnection; continuity; lesson; physics; mathematics; laboratory; absolute error; relative error; systematic error; gross error; indirect; direct